Host apoplastic cysteine protease activity is suppressed during the mutualistic association of Lolium perenne and Epichloë festucae. (25th February 2021) - Passarge, Andrea; Demir, Fatih; Green, Kimberly; Depotter, Jasper R L; Scott, Barry; Huesgen, Pitter F; Doehlemann, Gunther; Misas Villamil, Johana C
Abstract: Plants secrete various defence-related proteins into the apoplast, including proteases. Papain-like cysteine proteases (PLCPs) are central components of the plant immune system. To overcome plant immunity and successfully colonize their hosts, several plant pathogens secrete effector proteins inhibiting plant PLCPs. We hypothesized that not only pathogens, but also mutualistic microorganisms interfere with PLCP-meditated plant defences to maintain endophytic colonization with their hosts. Epichloë festucae forms mutualistic associations with cool season grasses and produces a range of secondary metabolites that protect the host against herbivores. In this study, we performed a genome-wide identification of Lolium perenne PLCPs, analysed their evolutionary relationship, and classified them into nine PLCP subfamilies. Using activity-based protein profiling, we identified four active PLCPs in the apoplast of L. perenne leaves that are inhibited during endophyte interactions. We characterized the L. perenne cystatin LpCys1 for its inhibitory capacity against ryegrass PLCPs. LpCys1 abundance is not altered during the mutualistic interaction and it mainly inhibits LpCP2. However, since the activity of other L. perenne PLCPs is not sensitive to LpCys1, we propose that additional inhibitors, likely of fungal origin, are involved in the suppression of apoplastic PLCPs during E. festucae infection. Abstract : Papain-like cysteine proteases (PLCPs) are hubs of the plant immune response. Here, we show that PLCP activity is suppressed in Lolium perenne during the interaction with the mutualistic endophyte Epichloë festucae .